Determinants of Ex-Ante Banking System Distress : A Macro-Micro Empirical Exploration of Some Recent Episodes - Gonzalez-Hermosillo, Brenda (IMF Working Papers; Working Paper, 1999)
This paper empirically analyzes the contribution of microeconomic and macroeconomic factors in five recent episodes of banking system problems in the U.S. Southwest (1986-92), Northeast (1991-92), and California (1992-93); Mexico (1994-95); and Colombia (1982-87). The paper finds that a low capital equity and reserve coverage of problem loans ratio is a leading indicator of bank distress, signaling a high likelihood of near-term failure. Distress is shown to be a function of the same fundamental macro-micro sources of risk that determine bank failures. Focusing on distress has the advantage that the fragility of the banking system can be assessed before a crisis actually occurs.